2011
DOI: 10.1186/1756-3305-4-228
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of vectors - Ixodiphagus hookeri and its Wolbachia symbionts in ticks in the Netherlands

Abstract: BackgroundIxodiphagus hookeri is a parasitic wasp of ixodid ticks around the world. It has been studied as a potential bio-control agent for several tick species. We suspected that the presence of Wolbachia infected I. hookeri eggs in ticks is responsible for incidental detection of Wolbachia DNA in tick samples.MethodsThe 28S rRNA and 16S rRNA genes of a specimen of I. hookeri was amplified and sequenced. PCR on part of the 28S rRNA gene was used to detect parasitic wasp DNA in 349 questing Ixodes ricinus tic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 33 publications
5
54
0
Order By: Relevance
“…Stafford et al (2003) reported that the prevalence of I. hookeri in host-seeking I. scapularis nymphs decreased from 25–30% to <1% as tick abundance decreased following deer removal. Recent studies from Europe indicate that these parasitoid wasps commonly are infected with Wolbachia and transfer these endosymbiotic bacteria to I. ricinus ticks (Tijsse-Klasen et al 2011, Plantard et al 2012). …”
Section: Suppression Of I Scapularis and B Burgdorferi With A Singlmentioning
confidence: 99%
“…Stafford et al (2003) reported that the prevalence of I. hookeri in host-seeking I. scapularis nymphs decreased from 25–30% to <1% as tick abundance decreased following deer removal. Recent studies from Europe indicate that these parasitoid wasps commonly are infected with Wolbachia and transfer these endosymbiotic bacteria to I. ricinus ticks (Tijsse-Klasen et al 2011, Plantard et al 2012). …”
Section: Suppression Of I Scapularis and B Burgdorferi With A Singlmentioning
confidence: 99%
“…For example, I. hookeri (Hymenoptera: Encyrtidae) is a wellknown parasitoid of ticks (Wood, 1911;Logan et al, 1985;Mwangi et al, 1994;Tijsse-Klasen et al, 2011). These wasps reproduce sexually, the female mating with the male immediately after emergence from the tick host (Hu et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Overall, highly varying rates of I. hookeri parasitization in host-seeking I. ricinus nymphs have been reported from Europe (22% in France, 7.2% in Italy, 2-4% in Germany, 9.6% in the Netherlands) (Collatz et al 2011;Tijsse-Klasen et al 2011;Plantard et al 2012;Ramos et al 2015). Whereas the rates of parasitization observed here were low (even considering minimum infection rates usually provide underestimates), higher rates in, for example, France and the Netherlands suggest that Ixodiphagus may have tangible impact on tick populations.…”
Section: Discussionmentioning
confidence: 99%
“…Ixodiphagus hookeri is an encyrtid wasp that specializes in parasitizing a wide range of hard tick species across the globe Knipling and Steelman 2000;Takasu and Nakamura 2008;Plantard et al 2012;Ramos et al 2015). In Europe, they parasitize both larvae and nymphs of I. ricinus, with nymphs appearing to be the preferred targets (Takasu and Nakamura 2008;Collatz et al 2011;Tijsse-Klasen et al 2011;Plantard et al 2012;Ramos et al 2015). Following oviposition, wasp eggs hatch into larvae that begin feeding on the tick only after it has finished its blood meal in the nymph stage, leading to the death of the tick prior to its development to an adult .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation